2018
DOI: 10.9734/ejmp/2018/41075
|View full text |Cite
|
Sign up to set email alerts
|

Antispasmodic and Myorelaxant Activity of Organic Fractions from Origanum majorana L. on Intestinal Smooth Muscle of Rodents

Abstract: Aims: Origanum majorana (Lamiaceae) is a herbaceous and perennial plant that is used in the Moroccan traditional medicine for treating gastrointestinal disorders. The objectives of this study were to confirm the antispasmodic and the myorelaxant activity of organic fractions of Origanum majorana (OM) in rat and rabbit jejunum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The method described by Makrane et al 10 was used. After having anesthetized the animal, the abdominal cavity was opened, and 2 cm jejunum was removed and preserved during the tests in the oxygenated standard Krebs-Henseleit buffer (KHB) solution with the following composition (in mM): NaCl 118, KCl 4.7, CaCl2 2.5, MgSO4 1.2, NaHCO3 25, KH2PO4 1.2 and glucose 10.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…The method described by Makrane et al 10 was used. After having anesthetized the animal, the abdominal cavity was opened, and 2 cm jejunum was removed and preserved during the tests in the oxygenated standard Krebs-Henseleit buffer (KHB) solution with the following composition (in mM): NaCl 118, KCl 4.7, CaCl2 2.5, MgSO4 1.2, NaHCO3 25, KH2PO4 1.2 and glucose 10.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…This hypothesis was confirmed when the extract shifted the carbachol dose-response curve to the right and down, inhibiting the contractile response of intestinal smooth muscle at increasing doses of carbachol. Therefore, this inhibitory effect is similar to that of a non-competitive antagonist to the cholinergic receptors (19). The antagonist binds to the receptor at a site separate from the agonist-binding site (allosteric site) and results in conformational changes in the receptor with a decreased affinity of the receptor for its agonist.…”
Section: These Waves Of Depolarization Activate Voltage-dependent Calcium Channels In the Smooth Muscle Cells Andmentioning
confidence: 84%
“…According to Godfraind et al (33), any substance that prevents these contractions (induced by the KCl rich medium) is considered to be an inhibitor of voltage-gated calcium channels. This hypothesis was reinforced by the fact that the extract at 0.1, 0.3, and 1 mg/ml shifted the dose-response curve of CaCl 2 to the right and down by inhibiting the response to increasing doses of calcium, therefore, this inhibitory effect is similar to that of a non-competitive antagonist to the voltage-dependent calcium channels (19). These findings are reinforced when we used verapamil, which is an antagonist of L-type voltage calcium channel blocker, which had an effect comparable to that of 1 mg/ml of ACAE.…”
Section: These Waves Of Depolarization Activate Voltage-dependent Calcium Channels In the Smooth Muscle Cells Andmentioning
confidence: 99%
“…Some of these studies presented detailed mechanistic explanations of the antispasmodic effect for the non-fractioned essential oils. Makrane et al [37] showed that organic fractions rich in essential oils from Origanum majorana showed a consistent spasmolytic effect on isolated rat and rabbit ileum not altered by atropine, L-NAME or methylene blue, and shifted to the right the concentrations-response curves for CaCl 2 , suggesting a calcium channel blocking effect. Rasheed et al [45] showed in an experiment on isolated rabbit jejunum that essential oil from Rosa indica relaxed the organ, shifting the calcium curves to the right, showing a similar effect to verapamil, a phenylalkylamine derivative from the calcium channel blocker class.…”
Section: Resultsmentioning
confidence: 99%